2013
DOI: 10.1007/s10484-013-9234-5
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Correlates of the Big 5: Autonomic Responses to Video Presentations

Abstract: Personality's link to emotional experience has been demonstrated, but specific biological responses to emotion as a function of personality have not been well-established. Here, the association between personality and physiological responses (heart rate, skin conductance, and respiration) to emotional videos was assessed. One-hundred sixty-nine participants self-reported on their Big 5 personality traits and underwent ambulatory monitoring as they watched four brief video clips from primetime television conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
4
13
2
1
Order By: Relevance
“…Additionally, Study 1 and 2 also indicated that, compared to participants low in extraversion, participants high in extraversion showed a more complete HR recovery after the first social stress. Overall, the present study, together with previous studies (Brumbaugh et al, 2013;Jonassaint et al, 2009), suggests a relative lesser cardiovascular reactivity and better cardiovascular recovery pattern to social or emotional stressors of individuals high in extraversion. These findings, to some extent, provide evidence that extraverts are associated with more favorable health outcomes.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Additionally, Study 1 and 2 also indicated that, compared to participants low in extraversion, participants high in extraversion showed a more complete HR recovery after the first social stress. Overall, the present study, together with previous studies (Brumbaugh et al, 2013;Jonassaint et al, 2009), suggests a relative lesser cardiovascular reactivity and better cardiovascular recovery pattern to social or emotional stressors of individuals high in extraversion. These findings, to some extent, provide evidence that extraverts are associated with more favorable health outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…As hypothesized, Study 1 and 2 indicated that, compared to participants low in extraversion, participants high in extraversion showed a relative lesser HR reactivity to the first and second social stress. Previous studies (Brumbaugh et al, ; Jonassaint et al, ) found that, in the stressors that are of relevance to the emotional nature of extraversion, individuals high in extraversion are more likely to show relative less cardiovascular reactivity as compared to individuals low in extraversion. Therefore, as the biopsychological theory of personality suggests, when the stressor contains social‐evaluative elements, extraverts may respond less strongly to the stressor because of their tendency to experience positive affect and adaptively cope with social situations (Eysenck & Eysenck, ; Jackson & Schneider, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Relatively high neuroticism has been reported as related to increased skin conductance in response to both unpleasant and pleasant pictures. However, this relationship was not replicated with induction by sad film clips (Reynaud, El Khoury-Mahalme, Rossier, Blin, & Khalfa, 2012;Brumbaugh, Kothuri, Marci, Siefert, & Pfaff, 2013).…”
Section: Personality and Emotional Reactivity: The Conceptual Frameworkmentioning
confidence: 84%
“…Os resultados sugerem que filmes com apelo emocional tendem a gerar aumentos na excitação autonômica e na atenção. As respostas fisiológicas parecem ser influenciadas principalmente pelo próprio conteúdo, com a personalidade exercendo um papel secundário, especialmente no direcionamento da atenção (Brumbaugh, Kothuri, Marci, Siefert, & Pfaff, 2013). De forma diferente, mas com o mesmo objetivo de investigar a relação entre personalidade e respostas autonômicas, 55 sujeitos foram expostos a imagens impressas com cargas afetivas positivas, negativas e neutras, e, nesse caso, a personalidade não foi capaz de influenciar suas respostas autonômicas causadas pelo estímulo (Mardaga, Laloyaux, & Hansenne, 2006).…”
Section: Principais Aplicações Em Marketingunclassified